RELIGION AND BANKING SYSTEM: THE FUTURE OF SYARIAH BANKING PRACTICES Historical and Contemporary Fiqh Perspectives - Hamka Siregar (Graduate Program of Pontianak Institute of Islamic Studies, 2014)
The momentum of the development of Sharia banking has been noticed since the 1970s, which generally had two patterns: first, establishing the Islamic bank side by side with conventional one (dual-banking system) as practiced in Egypt, Malaysia, Saudi Arabia, Jordan, Kuwait, Bahrain, and Bangladesh; and second, restructuring the banking system as a whole in accordance with Islamic Sharia (full-fledged Islamic financial system) as applied in Sudan, Iran and Pakistan. The development of the Sharia-based banks which have been established across the world since the 1970s, became the motivation of the Indonesian ulemas to draft law on Sharia banking, so that Sharia banking could also be developed. As a result, these last few years, the banking world in Indonesia has witnessed the establishment of the public Sharia banks and Sharia business units, like Bank Muamalat and Bank Syariah Mandiri to mention a few. Using historical and contemporary jurisprudence perspective, this paper provides discussion on the future of Sharia banking.